Improving the Ability to Story Daily Activities Through Picture Media in Grade 1 Students at St. Yohanes Tomohon 1 Catholic Elementary School - Deysti Trifena Tarusu; Savitska Runtu; Grace Moningka; Putri Ulyanda Manurung; Heppy Omega; Triniti Meinda F Tarore (Jurnal Multidisiplin Sahombu, 2026)
This study aims to improve the ability of first-grade students at St. Yohanes Tomohon Catholic Elementary School 1 to recount daily activities through pictures. The study used the Kemmis and McTaggart Classroom Action Research (CAR) model, implemented in one cycle. Twenty-eight students participated in the odd semester of the 2025/2026 academic year. Data were collected through observations of teacher and student activities, storytelling performance tests, short interviews, and documentation. The results showed an improvement in students' storytelling abilities, particularly in the aspects of speaking confidence, fluency, coherence, and vocabulary use for daily activities. Picture media is effective because it aligns with the concrete thinking developmental stage of lower-grade students and supports information processing through visual and verbal channels, as described in Dual Coding Theory. These findings align with several other studies that conclude that picture series can improve elementary school students' storytelling abilities.